Long COVID in long-term care: a rapid realist review - Annette Berndt; Valorie A Crooks; Manoj Sivan; Simon Carroll; Maura MacPhee; Shannon Freeman; Karen Davison; Ian Fyffe; Janice Sorensen; Alison Andrews-Paul; Jennifer Walls; Benajir Shams; et al. (BMJ Open)
Objectives The goals of this rapid realist review were to ask: (a) what are the key mechanisms that drive successful interventions for long COVID in long-term care (LTC) and (b) what are the critical contexts that determine whether the mechanisms produce the intended outcomes?Design Rapid realist review.Data sources Medline, CINAHL, Embase, PsycINFO and Web of Science for peer-reviewed literature and Google for grey literature were searched up to 23 February 2023.Eligibility criteria We included sources focused on interventions, persons in LTC, long COVID or post-acute phase at least 4 weeks following initial COVID-19 infection and ones that had a connection with source materials.Data extraction and synthesis Three independent reviewers searched, screened and coded studies. Two independent moderators resolved conflicts. A data extraction tool organised relevant data into context-mechanism-outcome configurations using realist methodology. Twenty-one sources provided 51 intervention data excerpts used to develop our programme theory. Synthesised findings were presented to a reference group and expert panel for confirmatory purposes.Results Fifteen peer-reviewed articles and six grey literature sources were eligible for inclusion. Eleven context-mechanism-outcome configurations identify those contextual factors and underlying mechanisms associated with desired outcomes, such as clinical care processes and policies that ensure timely access to requisite resources for quality care delivery, and resident-centred assessments and care planning to address resident preferences and needs. The underlying mechanisms associated with enhanced outcomes for LTC long COVID survivors were: awareness, accountability, vigilance and empathetic listening.Conclusions Although the LTC sector struggles with organisational capacity issues, they should be aware that comprehensively assessing and monitoring COVID-19 survivors and providing timely interventions to those with long COVID is imperative. This is due to the greater care needs of residents with long COVID, and coordinated efficient care is required to optimise their quality of life.